Double-Docking Technique, an Optimized Process for Intrathoracic Esophagogastrostomy in Robot-Assisted Ivor Lewis Esophagectomy - Wang, Fuqiang; Zhang, Hanlu; Qiu, Guanghao; Wang, Zihao; Li, Zhiyang; Wang, Yun (Frontiers in Surgery, 2022)
Background: Though the robotic Ivor Lewis esophagectomy has been increasingly applied, the intrathoracic esophagogastrostomy is still the technical barrier. In this retrospective study, we introduced a double-docking technique for intrathoracic esophagogastrostomy to optimize surgical exposure and facilitate intrathoracic anastomosis. Moreover, we compared the clinical outcomes between the double-docking technique and anastomosis with one docking procedure in robotic Ivor Lewis esophagectomy. Methods: From March 2017 to September 2020, the clinical data of 68 patients who underwent robotic Ivor Lewis esophagectomy was reviewed, including 23 patients who underwent double-docking technique (double-docking group) and 45 patients who underwent single-docking robotic esophagectomy (single-docking group). All patients were diagnosed with esophageal cancer or gastro-esophageal junction by biopsy before surgery. The technical details of double-docking technique were described in this paper. Results: There was no difference in the patient demographics data between two groups. The median surgical time in double-docking group was slightly shorter than in classic group without statistical difference (380min vs 395min, p=0.368). In double-docking group, the median blood loss was 90mL, the median number of lymph nodes harvest were 17 and the R0 resection rates were 100% (23/23). There were no differences in the surgical outcomes between two groups. Conclusions: Based on our experience, double-docking technique provides a good surgical exposure when fashioning anastomosis, and such technique dose not increase the surgical time. Therefore, we believe that the double-docking technique is a safe and effective method for intrathoracic esophagogastrostomy while providing a good exposure and ensuring the convenience and reliability of the intrathoracic anastomosis.